Interaction of Philosophy and Natural Sciences in Byzantine Empire - Zozulak, Jan (Communications - Scientific letters of the University of Zilina, 2018)
The aim of this paper is an analysis of the interaction of philosophy and natural sciences in Byzantine Empire. The cornerstone for this will be the clarification of the function of philosophy as a metascience (μεταεπιστήμη) in Greek thought, which grappled the order of things in its functional unity of macroscopic and microscopic observation of the world. This macroscopic observation was never at odds with microscopic research but was a universal science (καθόλου ἐπιστήμη) or science about scientifically knowable phenomena (ἡ μάλιστα ἐπιστήμη τοῦ μάλιστα ἐπιστητοῦ), that is, philosophy. Despite philosophy being an activity closely linked to natural sciences, it is not a science in itself, even though it is often mistaken for such as a term. Philosophy as knowledge, or a function that leads to knowledge, is called science (ἐπιστήμη), but this does not make it equal to scientific disciplines. In the unity of all scientific disciplines, which are hierarchically ordered into a pyramid, philosophy always stands on top, it being a science about scientifically knowable phenomena. Out of all the scientific disciplines, philosophy is the one that leads to knowledge of first beginnings and causes. It is a general observation of reality, which secures the unity of scientifically knowable facts and phenomena. Philosophical knowledge as a “universal science” (καθόλου ἐπιστήμη) concentrates all partial findings into a unified whole. Philosophy is continually attempting to reach a global understanding, while science focuses on a microscopic observation of a specific part of the system.